Primary atrophic profound linear scleroderma - Tarlow, Mordechai M. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
We describe an 18-year-old male with primary atrophic profound linear scleroderma. It was not preceded by an inflammatory reaction or sclerosis, butit involved the subcutaneous and deeper tissues of the fingers. It did not involve the dermis, or show either discoloration or changes in texture. Involvement of deeper tissue and the progression of the disease suggest atypical primary atrophic profound linear scleroderma. Our case of primary atrophic profound linear scleroderma appears to be a unique variant of localized scleroderma.
Keywords: Adult; Atrofija; Atrophy; Biopsija; Biopsy; dermatologija; Diagnosis; kožne bolezni; Odrasli; Pathology; Scleroderma, Circumscribed; sklerodermija; Sklerodermija cirkumskriptna